Prevalence and Determinants of Mobile Health Applications Usage: A National Descriptive Study - Amer, Samar A.; Bahumayim, Ayah; Shah, Jaffer; Aleisa, Nouf; Hani, Basma M.; Omar, Doaa I. (Frontiers in Public Health, 2022)
We aimed to determine the prevalence of MHAs’ usage and explore the context and determinants of using MHAs among inhabitants in Saudi Arabia (SA). This cross-sectional study randomly selected 679 adult inhabitants from the 20 health regions in SA through an electronic, self-administered, well-structured, validated, Arabic questionnaire. The prevalence of using MHAs was 47.9%, and it was significantly higher among younger, Saudi, highly educated, and working participants, as well as those with chronic diseases (p<0.05). The main motives of using MHAs were to promote the health status (in 68.6%) and to lose weight (in (33.2%). The most used apps were related to daily steps-counting (54.2%), and among females was tracking ovulation period apps (43.5%). The most common reported advantage of using MHAs was saving time (64%). Despite the potential benefits of MHAs, they were used only in nearly half of the studied participants in SA. The most effective MHAs in improving health status were exercise, calorie-related, water uptake, and daily steps-counting apps. Policymakers globally looking to address reform aimed at improving health with mobile apps will find our study to be interesting. mobile apps will find this study of interest.